Interest in History and its Implications on the Economy - Nurjannah; Rukmanasari, Ita; Misbahuddin; Siradjuddin (LAA MAISYIR: Jurnal Ekonomi Islam, 2023)
Three conventional economic thinkers, namely Plato, Aristotle and Thomas Aquinas, criticized the interest system, which was in line with the Islamic economic system. This research aims to explain the views of these three figures regarding interest and prove that the prohibition of usury is not just a sharia rule but has great harm. This research includes mix-method research, qualitative with a field research approach, quantitative with linear regression tests. The research results show that Plato, Aristotle and Thomas Aquinas viewed usury as injustice and had an impact on disputes and the accumulation of wealth. Usury creates individuals who love wealth, are consumptive, find it difficult to forgive, have an unstable soul, deify money, loss of wealth and economic shocks, while for the State it has an impact on inflation, economic crisis, decoupling, hostility and inequality. The effect of interest rates and GDP is negative, meaning that the higher the interest rate, the lower the added value of business units in Indonesia. It is hoped that this article can support the development of sharia economics and avoid all forms of interest in the economy.